The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1116/1.2162566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stress on the evolution of mask-edge defects in ion-implanted silicon

Abstract: Articles you may be interested inStudy of millisecond laser annealing on recrystallization, activation, and mobility of laser annealed SOI doped via arsenic ion implantation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…The ͓110͔ stress ͑ ͓110͔ ͒ was calculated using the ͓110͔ Young's modulus of Si near ϳ500°C ͑ϳ1.61ϫ 10 11 Pa͒, the wafer halfthickness, and the local radius of curvature as presented elsewhere. 10,11 Maximum repeatable stresses of 1.5± 0.1 GPa were attained. Specimens were annealed at 525°C in N 2 ambient for 0.7-3.2 h. Stress-free, tensile, and compressive specimens were annealed simultaneously for each anneal time.…”
mentioning
confidence: 95%
“…The ͓110͔ stress ͑ ͓110͔ ͒ was calculated using the ͓110͔ Young's modulus of Si near ϳ500°C ͑ϳ1.61ϫ 10 11 Pa͒, the wafer halfthickness, and the local radius of curvature as presented elsewhere. 10,11 Maximum repeatable stresses of 1.5± 0.1 GPa were attained. Specimens were annealed at 525°C in N 2 ambient for 0.7-3.2 h. Stress-free, tensile, and compressive specimens were annealed simultaneously for each anneal time.…”
mentioning
confidence: 95%
“…Finally, stress can influence the shape of a regrowing ␣/crystalline interface and it is worthwhile to consider this as stress from trench structures can be significant. 14,15 However, because both SiO 2 -filled and SiO 2 -free trench structures exhibited similar regrowth interfaces, the observations are likely not stress-related.…”
mentioning
confidence: 95%
“…However, it is important to consider the role that applied stress may have on the SPEG process in patterned material, since the presence of stresses of substantial magnitude is ubiquitous in current Si-based device fabrication (Hu, 1991). Interestingly, extensive prior work showed that the application of different forms of mechanical stress during SPEG could alter the morphology of the evolving growth interface thus favoring or impeding mask-edge defect formation (Olson et al, 2006;Rudawski et al, 2006Rudawski et al, , 2008aRudawski et al, , 2009bShin et al, 2001a,b,c). Specifically, when uniaxial tension was applied along the in-plane [110] direction during SPEG, the impingement of the two portions of the growth interface was retarded, which resulted in defect-free growth (Olson et al, 2006;Rudawski et al, 2006Rudawski et al, , 2008aRudawski et al, , 2009b.…”
Section: Stress Effectsmentioning
confidence: 94%
“…Interestingly, extensive prior work showed that the application of different forms of mechanical stress during SPEG could alter the morphology of the evolving growth interface thus favoring or impeding mask-edge defect formation (Olson et al, 2006;Rudawski et al, 2006Rudawski et al, , 2008aRudawski et al, , 2009bShin et al, 2001a,b,c). Specifically, when uniaxial tension was applied along the in-plane [110] direction during SPEG, the impingement of the two portions of the growth interface was retarded, which resulted in defect-free growth (Olson et al, 2006;Rudawski et al, 2006Rudawski et al, , 2008aRudawski et al, , 2009b. In contrast, when uniaxial compression was applied along the in-plane [110] direction during SPEG, the impingement of the two portions of the growth interface was enhanced, which resulted in defective growth (Olson et al, 2006;Rudawski et al, 2006Rudawski et al, , 2008aRudawski et al, , 2009b.…”
Section: Stress Effectsmentioning
confidence: 96%